2017
DOI: 10.1007/s40670-017-0405-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Medical Spanish Elective for Senior Medical Students: Improving Outcomes through OSCE Assessments

Abstract: Background There is no standardized curriculum or assessment method that addresses Spanish skills in U.S. medical schools. The authors implemented a 10-week Clinical Medical Spanish elective for fourth-year medical students. Methods Data were collected for 58 students from 2013 to 2015 pertaining to pre- and post-course self-evaluation of Medical Spanish comfort level and Objective Structured Clinical Examinations. Results Student comfort level with Spanish-speaking patients improved for performing history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
1
25
0
4
Order By: Relevance
“…Many factors may contribute to this improvement, such as frequency of language use in personal and professional settings, travel to countries where the language is spoken, and additional courses taken since graduating from HMS. Nevertheless, our findings suggest that in general, the self-reported langauge proficiency of alumni improved since taking the course, supporting other reports that have shown improvement in the oral proficiency of students before and after taking medical language courses [ 18 20 ]. Acknowledging that it has been several decades since some respondents took a medical language course at HMS, we cannot conclude that the courses alone are responsible for the increase in proficiency.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many factors may contribute to this improvement, such as frequency of language use in personal and professional settings, travel to countries where the language is spoken, and additional courses taken since graduating from HMS. Nevertheless, our findings suggest that in general, the self-reported langauge proficiency of alumni improved since taking the course, supporting other reports that have shown improvement in the oral proficiency of students before and after taking medical language courses [ 18 20 ]. Acknowledging that it has been several decades since some respondents took a medical language course at HMS, we cannot conclude that the courses alone are responsible for the increase in proficiency.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is no current estimate of how many schools offer non-Spanish medical language courses. Students who take Medical Spanish courses have shown improvements in listening comprehension skills, oral fluency, and comfort level working with Spanish-speaking patients [ 18 20 ]. In addition, a national survey found that 85% of medical students and trainees are interested in improving their Medical Spanish skills, suggesting that there is strong motivation to provide language-concordant care amongst trainees [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formal elective is designed to provide 2 weeks (80 h) of official credit spread out over a 10-week longitudinal elective, in which students have a 2-h evening lecture weekly, but have multiple self-study multimedia and grammar/vocabulary exercise components, 17 patient interview requirements, mid- and end-course objective structured clinical examinations with trained standardized patients (SPs), and cultural research spread out over the course. 18…”
Section: Curricular Models For Dedicated Medical Spanishmentioning
confidence: 99%
“…Eighty-nine percent of follow-up respondents reported that the elective was useful for their intern year, and 97.3% reported that they would recommend the course to other fourth-year medical students. 18 To accommodate student need, a new 2-week intensive course will be piloted in the near future at UICOM, in which the curriculum will be condensed into a shorter time period, but students will dedicate to medical Spanish material full-time for the 2 weeks of the course.…”
Section: Curricular Models For Dedicated Medical Spanishmentioning
confidence: 99%
“…Regardless of their cultural background or knowledge-base, providers who treat the Latino population may have never been exposed to communication skills education to address the healthcare needs of this patient population in their preferred language. Medical Spanish programs exist at some medical institutions but mostly target practicing health professionals, medical students, or residents [13].…”
Section: Introductionmentioning
confidence: 99%